Răspuns :
13xy+13y+12x+11=0
scadem 12 x din ambele parti
13xy+13y+12x+11-12x=0-12x
13xy+13y+11=-12x
scadem 11 din ambele parti
13xy+13y+11-11= -12x-11
13xy+13y=-12x-11
13y(x+1)=-12x-11
impartim in ambele parti cu 13(x-1)
[tex] \frac{13y(x+1)}{13(x+1)}= \frac{-12x}{13(x+1)}}- \frac{11}{13(x+1)} \\ \\ y= \frac{-12x-11}{13(x+1)}; x \neq -1 [/tex]
scadem 12 x din ambele parti
13xy+13y+12x+11-12x=0-12x
13xy+13y+11=-12x
scadem 11 din ambele parti
13xy+13y+11-11= -12x-11
13xy+13y=-12x-11
13y(x+1)=-12x-11
impartim in ambele parti cu 13(x-1)
[tex] \frac{13y(x+1)}{13(x+1)}= \frac{-12x}{13(x+1)}}- \frac{11}{13(x+1)} \\ \\ y= \frac{-12x-11}{13(x+1)}; x \neq -1 [/tex]